Employee Stock Options and Real Earnings Management through Accretive Share Buyback in Malaysia - Alquhaif, Abdulsalam Saad; Abdul Latif, Rohaida; Chandren, Sitraselvi (Journal of Advanced Research in Business and Management Studies, 2020)
We examine the association between employee stock options and real earnings management through accretive buyback programs. Our study uses unbalanced panel logistic estimation model for a sample of 601 firms’ observations that involved in accretive share buyback over the period 2010-2015. The outcomes reveal that stock options exercised by insiders (executives and employees) are associated with high likely to engage in accretive share buyback activities. The results also provide evidence that a large percentage of the independent directors serving the board constrain real earnings management by engaging in accretive share buybacks. Our study contributes to the debate on stock options, and their impact on accretive buyback programs to manage reported EPS. Our findings provide insight to investors and the policymakers that managers holding stock options have more incentive to manage EPS through accretive share buyback activities. Academic researchers could extend this study by separating among executive and employees’ stock options and between exercisable and non-exercisable stock options.